Influence of remnant lipoprotein particle cholesterol on non-target lesions progression in patients undergoing percutaneous coronary intervention - Liu, Jing; Teng, Tian-Qi; Li, Zheng; Hu, Feng-Wang; Sha, Wei-Wei; Shen, Chang-Xian; Xia, Yong; Zhang, Yao-Jun; Liang, Li (Frontiers in Cardiovascular Medicine, 2024)
BackgroundLow-Density Lipoprotein Cholesterol (LDL-C) is the primary lipid therapy target for coronary artery disease (CAD) patients after percutaneous coronary intervention (PCI). However, progression of coronary atherosclerosis occurs even LDL-C controlled well, some potentially important factors have been overlooked.ObjectiveThis study aims to elucidate the relationship between remnant lipoprotein particle cholesterol (RLP-C) and the progression of non-target lesions (NTLs) in patients with well-controlled lipid levels after PCI.MethodsThis retrospective study included 769 CAD patients who underwent PCI and followed up angiography within 6–24 months thereafter. Employing Multivariate Cox regression analysis, we assessed the correlation between RLP-C and NTLs progression. Based on the receiver operating characteristic curve analysis, we identified the optimal cutoff point for RLP-C, following which the patients were divided into two groups. Propensity score matching balanced confounding factors between groups, and Log-rank tests compared Kaplan–Meier curves for overall follow-up to assess NTLs progression.ResultsMultivariate Cox analysis revealed an independent association between RLP-C and NTLs progression when LDL-C was well-controlled. Additionally, the RLP-C level of 0.555 mmol/L was determined to be the best value for predicting NTLs progression. Following propensity score matching, Kaplan–Meier curves illustrated a significantly higher cumulative rate of NTLs progression in patients with RLP-C levels ≥0.555 mmol/L compared to the others (Log-rank P = 0.002). Elevated RLP-C levels were associated with high triglyceride concentrations, diabetes mellitus, and increased risk of revascularization.ConclusionsThis study illustrated the atherogenic impact of RLP-C in CAD patients. High RLP-C levels increased the risk of revascularization.